2014
DOI: 10.1021/jf5030592
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Kelch-like ECH-Associated Protein 1 (Keap1)/NF-E2-Related Factor 2 (Nrf2) Pathway through Covalent Modification of the 2-Alkenal Group of Aliphatic Electrophiles in Coriandrum sativum L.

Abstract: Phytochemicals able to activate the transcription factor NF-E2-related factor 2 (Nrf2) were isolated from an extract of Coriandrum sativum L. (C. sativum) leaves by preparative octadecyl silica column chromatography. Ultraperformance liquid chromatography and liquid chromatography-tandem mass spectrometry analysis of the isolated components after derivatization with 2-diphenylacetyl-1,3-inandione-1-hydrazone and experiments with HepG2 cells revealed that (E)-2-alkenals with different carbon numbers play a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Under normal conditions, the oxidative sensor protein Keap1 retains Nrf2 in the cytosol and acts as an adaptor for an E3 ligase to degrade Nrf2 through an ubiquitin-proteasome system (52). Oxidative stresses (such as reactive oxygen species (ROS)) and other electrophiles (including aldehydes) modify the cysteine residues in Keap1, causing Nrf2 activation, which in turn promotes the transcriptions of its target genes involved in oxidative stress resistance and cell survival (37,53). Disruption of Keap1 and overexpression of Nrf2 in mice independently induce hyperproliferation in keratinocytes and skin barrier defect phenotypes such as increased TEWL and hyperkeratosis (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, the oxidative sensor protein Keap1 retains Nrf2 in the cytosol and acts as an adaptor for an E3 ligase to degrade Nrf2 through an ubiquitin-proteasome system (52). Oxidative stresses (such as reactive oxygen species (ROS)) and other electrophiles (including aldehydes) modify the cysteine residues in Keap1, causing Nrf2 activation, which in turn promotes the transcriptions of its target genes involved in oxidative stress resistance and cell survival (37,53). Disruption of Keap1 and overexpression of Nrf2 in mice independently induce hyperproliferation in keratinocytes and skin barrier defect phenotypes such as increased TEWL and hyperkeratosis (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the p K a of a Cys thiol is decreased when it is proximal to basic amino acids such as lysine, histidine, or arginine, it is possible that a variety of quinones can covalently bind to AhR through the Cys residues, leading to the induction of CYP1A1 because little appreciable modification of HSP90 was detected under the conditions. As mentioned above, our group has demonstrated that the activation of effector molecules is coupled to the covalent attachment of environmental electrophiles to sensor proteins. ,,,,,,, AhR activation by 1,2-NQ is the first example of activation of a redox signal transduction through direct arylation of the transcription factor by environmental quinones.…”
Section: Dual Role Of Electrophiles In Redox Signal Transductionsmentioning
confidence: 95%
“…As mentioned above, our group has demonstrated that the activation of effector molecules is coupled to the covalent attachment of environmental electrophiles to sensor proteins. 19,37,84,85,88,96,164,175 AhR activation by 1,2-NQ is the first example of activation of a redox signal transduction through direct arylation of the transcription factor by environmental quinones.…”
Section: Activation Of Redoxmentioning
confidence: 99%
See 1 more Smart Citation
“…In many oxidative stress animal models, PKCε is closely associated with lung injury, either by drug blockade or by gene knockout (Liu, et al., 2017 ; Yadav et al., 2018 ). The cytoplasm‐localized transcription factor Nrf2 is closely related to oxidative stress (Je & Lee, 2015 ; Zhu et al., 2017 ) and induces transcription of many ARE‐dependent target genes (Abiko et al., 2014 ; Zhong & Kowluru, 2012 ), including HO‐1. HO‐1 expression is increased under oxidative stress and plays an antioxidant role in the pathological development of various diseases (Dias‐Teixeira et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%